Long-term Effect of Dual-focus Contact Lenses on Myopia Progression in Children: A 6-year Multicenter Clinical Trial. Issue 3 (27th March 2022) - Chamberlain, Paul; Bradley, Arthur; Arumugam, Baskar; Hammond, David; McNally, John; Logan, Nicola S.; Jones, Deborah; Ngo, Cheryl; Peixoto-de-Matos, Sofia C.; Hunt, Chris; Young, Graeme
Abstract : SIGNIFICANCE: Treatment of myopic children with a dual-focus soft contact lens (DFCL; MiSight 1 day) produced sustained slowing of myopia progression over a 6-year period. Significant slowing was also observed in children switched from a single vision control to treatment lenses (3 years in each lens). PURPOSE: This study aimed to evaluate the effectiveness of DFCLs in sustaining slowed progression of juvenile-onset myopia over a 6-year treatment period and assess myopia progression in children who were switched to a DFCL at the end of year 3. METHODS: Part 1 was a 3-year clinical trial comparing DFCLs with a control contact lens (Proclear 1 day) at four investigational sites. In part 2, subjects completing part 1 were invited to continue for 3 additional years during which all children were treated with MiSight 1 day DFCLs (52 and 56 from the initially treated [T6] and control [T3] groups, respectively). Eighty-five subjects (45 [T3] and 40 [T6]) completed part 2. Cyclopleged spherical equivalent refractive errors (SEREs) and axial lengths (ALs) were monitored, and a linear mixed model was used to compare their adjusted change annually. RESULTS: Average ages at part 2 baseline were 13.2 ± 1.3 and 13.0 ± 1.5 years for the T6 and T3 groups, respectively. Slowed myopia progression in the T6 group observed during part 1 was sustained throughout part 2 (mean ± standard error of the mean: change from baseline SERE [in diopters], −0.52 ± 0.076 vs. −0.51 ± 0.076; change in AL [in millimeters], 0.28 ± 0.033 vs. 0.23 ± 0.033; both P > .05). Comparing progression rates in part 2 for the T6 and T3 groups, respectively, indicates that prior treatment does not influence efficacy (SERE, −0.51 ± 0.076 vs. −0.34 ± 0.077; AL, 0.23 ± 0.03 vs. 0.18 ± 0.03; both P > .05). Within-eye comparisons of AL growth revealed a 71% slowing for the T3 group (3 years older than part 1) and further revealed a small subset of eyes (10%) that did not respond to treatment. CONCLUSIONS: Dual-focus soft contact lenses continue to slow the progression of myopia in children over a 6-year period revealing an accumulation of treatment effect. Eye growth of the initial control cohort with DFCL was slowed by 71% over the subsequent 3-year treatment period.